The ciprofloxacin target AUC : MIC ratio is not reached in hospitalized patients with the recommended dosing regimens. (14th December 2012) - Haeseker, Michiel; Stolk, Leo; Nieman, Fred; Hoebe, Christian; Neef, Cees; Bruggeman, Cathrien; Verbon, Annelies
<x xml:space="preserve">Abstract</x> WHAT IS ALREADY KNOWN ABOUT THIS SUBJECT The efficacy target of AUC : MIC > 125 is based on the study of Forrest et al. in 1993. Recent studies have shown that in ICU patients the ciprofloxacin efficacy target of AUC : MIC > 125 is often not reached. WHAT THIS STUDY ADDS The efficacy targets of ciprofloxacin in patients in general wards are often not reached. Most patients have low AUC with current i.v. dosing regimens. We suggest increasing the standard dose of ciprofloxacin to 1200 mg intravenously 24 h–1. Patients in general wards have high interindividual variability of pharmacokinetic parameters and therapeutic drug monitoring could be useful to support dosing. AIM The aim of this study was to determine the ciprofloxacin serum concentrations in hospitalized patients and to determine which percentage reached the efficacy target of AUC : MIC > 125. Additionally, the influence of demographic anthropomorphic and clinical parameters on the pharmacokinetics and pharmacodynamics of ciprofloxacin were investigated. METHODS In serum of 80 hospitalized patients ciprofloxacin concentrations were measured with reverse phase high performance liquid chromatography with fluorescence detection. The ciprofloxacin dose was 400–1200 mg day−1 i.v. in two or three doses depending on renal function and causative bacteria. Pharmacokinetic parameters were calculated with maximum a posteriori Bayesian estimation (MW\PHARM 3.60). A two compartment open model was used. RESULTS Mean (± SD) age was 66 (± 17) years, the mean clearance corrected for bodyweight was 0.24 l h−1 kg−1 and the mean AUC was 49 mg l−1 h. Ciprofloxacin clearance and thus AUC were associated with both age and serum creatinine. Of all patients, 21% and 75% of the patients, did not reach the proposed ciprofloxacin AUC : MIC > 125 target with MICs of 0.25 and 0.5 mg l−1, respectively. A computer simulated increase in the daily dose from 800 mg to 1200 mg, decreased these percentages to 1% and 37%, respectively. CONCLUSION A substantial proportion of the hospitalized patients did not reach the target ciprofloxacin AUC : MIC and are suboptimally dosed with recommended doses. Taking into account the increasing resistance to ciprofloxacin worldwide, a ciprofloxacin dose of 1200 mg i.v. daily in patients with normal renal function is necessary to reach the targeted AUC : MIC > 125.